The Effectiveness of Using Problem Based Learning through Audio Visual Media to Improve Students’ Critical Thinking in Colloidal Material - Rizka Leonita Wibowo; Ratu Betta Rudibyani; Emmawaty Sofya (Universitas Lampung, 2021)
This research aims to the effectiveness of using audio-visual media based on problem-based learning to improve students' critical thinking ability on colloidal material course. The population of this research is XI MIPA students at SMAN 14 Bandar Lampung. The sample of this research is XI MIPA 6 as the experimental class and XI MIPA 4 as the control class. In this research, the method used is quasi experiment with the pretest-posttest control group design. The effectiveness of using problem based learning through audio visual media to improve students' critical thinking ability on colloidal materials is measured by the significant average of the n-Gain score between experiment and control class. The result shows that the n-Gain score of students’ critical thinking in the experimental class is 0.81 that is categorized “high”, and for the control class is 0.63 that is categorized “medium”. The effect size test results show that problem based learning through audio visual media has a